2014
DOI: 10.1177/1934578x1400900404
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modifications of Cinchona Alkaloids Lead to Enhanced Inhibition of Human Butyrylcholinesterase

Abstract: Butyrylcholinesterase (BChE) inhibitors were identified from a collection containing cinchonine, cinchonidine and synthetic derivatives, and further characterized using cytotoxicity and molecular docking studies. The most active ones were: (10≡)-10,11-dibromo-10,11-dihydrocinchonidine (11), a competitive inhibitor with K i = 3.45±0.39 µM, and IC 50 BChE = 9.83±0.30 µM / human (h)BChE = 34.47±4.63 and O-(trimethylsilyl)cinchonine (15), a mixed inhibitor with K iuc = 1.73±0.46 µM and K ic = 0.85±0.26 µM, and IC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…This observation is in accordance with results by Nawaz et al [ 22 ], where cinchonine quaternized with anthracene was about a 110 times more potent inhibitor than cinchonine without a substituent. The inhibition potency of CD-Met toward human BChE determined here is similar to that for equine BChE determined previously [ 23 ]. The K s values derived from the kinetics of inhibition were very close to BChE’s previously determined Michaelis-Menten constant ( K M ) [ 7 ], which implies binding of the tested compounds to the catalytic site of BChE.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…This observation is in accordance with results by Nawaz et al [ 22 ], where cinchonine quaternized with anthracene was about a 110 times more potent inhibitor than cinchonine without a substituent. The inhibition potency of CD-Met toward human BChE determined here is similar to that for equine BChE determined previously [ 23 ]. The K s values derived from the kinetics of inhibition were very close to BChE’s previously determined Michaelis-Menten constant ( K M ) [ 7 ], which implies binding of the tested compounds to the catalytic site of BChE.…”
Section: Resultssupporting
confidence: 84%
“…Furthermore, these alkaloids are bioactive and are used in treating malaria and fever, while some also possess analgesic, anti-inflammatory and antiarrhythmic properties [ 21 ]. Recently, some cinchonine and cinchonidines were proven to be up to 100 times more potent inhibitors for equine BChE than human AChE, while anthracene/benzyl modified cinchonidine has been identified as selective BChE inhibitors with a BChE/AChE selectivity ratio of 250 [ 22 , 23 ]. In addition, a high affinity for binding to the active site of BChE was determined for some Cinchona oxime compounds studied as reactivators of OP-inhibited human BChE [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The oximes inhibited both cholinesterases in micromolar range but showed a strong preference for binding to hBChE. This confirmed previous studies on similar compounds [ 13 , 14 ] but also indicated that the addition of the oxime moiety did not influence their ability to bind to the cholinesterases active site. Moreover, the evaluated dissociation inhibition constants ( K i ) were higher than those published for pyridinium oximes and hAChE [ 22 , 23 , 24 ], and were 10–100-fold lower for pyridinium and imidazolium oximes and hBChE [ 17 , 25 ].…”
Section: Resultssupporting
confidence: 89%
“…This paper reports on the synthesis of three derivatives of Cinchona oxime compounds. Some derivatives of cinchonidine have been identified as inhibitors of cholinesterases fitting their active site [ 13 , 14 ]. Therefore, we found them interesting for oxime moiety addition and their evaluation as reactivators of human AChE (hAChE) and BChE (hBChE) inhibited by OPs.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that compounds based on a quinoline structure are potent inhibitors of both cholinesterases, acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) [2,3]. As their primary structural motive, these compounds have tacrine or quinidine moiety [4][5][6][7][8][9]. Furthermore, anticholinesterase activity has been confirmed for antimalarial drugs chloroquine, hydroxychloroquine and primaquine [10][11][12].…”
Section: Introductionmentioning
confidence: 99%